O coordenador de curso superior e a autopercepção do PsyCap - Silva, Andreia Bonato da (Universidade do Vale do Rio dos Sinos, 2015)
This study is characterized by being a field research of quantitative and qualitative approach, which was conducted with 309 coordinators of private higher education from RS. This research aimed to know the perception of these managers/professors about their Psychological Capital (PsyCap) and the ability to generate it in the professors whom they work with. Thus, the PCQ (24) was applied, through electronic survey sent to participants by email and semi-structured interviews conducted with 10 coordinators. The results show that several operational activities are assigned for the manager/professor that causes him/her to have difficulties to manage the course. As for the Psychological Capital, the results pointed to a higher average in efficacy for men, while optimism was higher in women. The time as coordinator did not appear to influence the four PsyCap dimensions, but the time from experience in the university environment showed that the coordinators, who are between 5-10 years into it, were those with the best average in the four dimensions PsyCap. Regarding the ability to generate Psychological Capital in professors, through the inventory of critical incidents, applied in the second part of the interview, it was clear that the coordinators, even with involvement overload with bureaucratic processes can still stimulate, in addition to teachers, peers and also students in the four dimensions of PsyCap. These results point to a need of review by these IES about the role of higher education coordinator, his/her power, activities and competencies because higher education market is competitive and also because, a provision of courses is greater than the demand and the requirements of structural quality and organizational required by the MEC are higher. Thus, the possibility that the coordinator will come effectively act as a leader, stimulating teachers, pupils and peers in the dimensions of Psychological Capital may become a more frequent occurrence, causing the institution to gain in quality educational management and consequent improvement in work performance of this professional as well as their professors.
Keywords: Curso superior; Coordenadores; PsyCap; Autopercepção; Capital psicológico; Psychological Capital; Coordinators; ACCNPQ::Ciências Sociais Aplicadas::Administração